Supervisi Pendidikan dan Peningkatan Mutu Sekolah: Studi Literatur Tentang Praktik dan Dampaknya - Gilang Syahputra; M. Jaya Adi Putra; Fadly Azhar (Comit: Communication, Information and Technology Journal, 2025)
Educational supervision is a strategic instrument for improving the quality of education in schools. This study aims to analyse various practices in the implementation of educational supervision and its impact on school quality enhancement based on a literature review. The method used is a systematic literature study of scientific articles, research reports, and policy documents that are certainly relevant to educational supervision and improving school quality. The findings show that effective educational supervision is characterized by a collaborative approach, a focus on improving teacher competence, and support from responsive school leadership and policies. Supervision that is carried out consistently and professionally has been proven to contribute positively to the quality of learning processes, teacher performance, and the development of a quality culture within schools. However, challenges remain, including limited supervisory competencies, a lack of continuous training, and teacher resistance to the supervision process. This review recommends strengthening a supervision system based on coaching and reflection, as well as improving human resource capacity as key efforts to achieve sustainable educational quality.